Bank's Responsibility for Customer Money Losses in Inter-Bank Transfer Errors (Study of Decision No. 148/PID.SUS/2021/PN SBY) - Sitorus, Rolib; Saphira, Felicia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the bank's responsibility for customer money losses in the event of an interbank transfer error in case NO 148/PID.SUS/2021/PN SBY ​​and how legal protection for customers for losses due to incorrect transfers in the decision (NO 148/PID.SUS/2021/PN SBY). The research method used by the author in this study is the juridical-normative legal research method. The juridical-normative method is an approach carried out by examining the approach of theories, concepts, reviewing laws and regulations related to this research or the legislative approach. Normative juridical research is legal research that positions law as a building of a normative system. The normative system in question is regarding the principles, norms, rules of laws and regulations, agreements and doctrines (teachings). This normative research is research on legal systematics, namely research whose main purpose is to identify the definitions or bases in law. Based on the results of the study, it shows that the bank's accountability carried out in accordance with applicable legal provisions is the management of PT. Bank BCA has admitted to making efforts to resolve the matter through deliberation and Ardi (as the recipient of the wrongly transferred funds) based on Bank BCA's records, Ardi was given 2 (two) notification letters of the wrong transfer and BCA has asked him to return the funds since March 2020 and Bank BCA has issued a warning to Ardi. If the bank makes a mistake in transferring funds, they must prove that there has been an error in sending, and if they find out, the bank must immediately collect the funds.